Gør køn en forskel? - Hvad fortæller studerende på universitetet om køn og studier på nordisk og kemi? - Reisby, Kristen (Kvinder, Køn & Forskning, 2000)
The article deals with what female and male students at two different university studies explicitly say about gender differences in qualitative group and individual interviews. The female students are very critical and sometimes selfcritical of the social intercourse of women and of female social communities of practice, and describe male students’ ways of interacting and masculine values as a counterpart. The interviews with male students contain less critical statements on their own social and professional attitudes and ways of interacting, but some negative statements on female social communities and female students’ way of studying. The article discusses how these differences can be understood and in what way they might be a barrier for female students’ development of an academic professionalism.